Cement augmentation of odontoid peg fractures: the effect of cement volume and distribution on construct stiffness - Capek, Lukas; Rehousek, Petr; Henys, Petr; Bleibleh, Sabri; Jenner, Edward; Kulvajtova, Marketa; Skala-Rosenbaum, Jiri (European spine journal, 2020)
PURPOSE: The cement augmentation of a conventional anterior screw fixation in type II odontoid process fractures for elderly patients significantly increased stiffness and load to failure under anterior-posterior load in comparison with non-augmented fixation. The amount and quality of bone cement are usually taken ad hoc in clinical practise. In this study, we wanted to clarify the role of bone cement amount and its quality to the stiffness of odontoid and vertebrae body junction. METHODS: Finite-element method was used to achieve different scenarios of cement augmentation. For all models, an initial stiffness was calculated. Model (1) the intact vertebrae were virtually potted into a polymethylmethacrylate base via the posterior vertebral arches. A V-shaped punch was used for loading the odontoid in an anterior-posterior direction. (2) The odontoid fracture type IIa (Anderson-D'Alonzo classification) was achieved by virtual transverse osteotomy. Anterior screw fixation was virtually performed by putting self-drilling titanium alloy 3.5 mm diameter anterior cannulated lag screw with a 12 mm thread into the inspected vertebrae. A V-shaped punch was used for loading the odontoid in an anterior-posterior direction. The vertebrae body was assumed to be non-cemented and cemented with different volume. RESULTS: The mean cement volume was lowest for body base filling with 0.47 ± 0.03 ml. The standard body filling corresponds to 0.95 ± 0.15 ml. The largest volume corresponds to 1.62 ± 0.12 ml in the presence of cement leakage. The initial stiffness of the intact C2 vertebrae was taken as the reference value. The mean initial stiffness for non-porous cement (E = 3000 MPa) increased linearly (R2 = 0.98). The lowest stiffness (123.3 ± 5.8 N/mm) was measured in the intact C2 vertebrae. However, the highest stiffness (165.2 ± 5.2 N/mm) was measured when cement leakage out of the odontoid peg occurred. The mean initial stiffness of the base-only cemented group was 147.2 ± 8.4 N/mm compared with 157.9 ± 6.6 N/mm for the base and body cemented group. This difference was statistically significant (p < 0.0061). The mean initial stiffness for porous cement (E = 500 MPa) remains constant. Therefore, there is no difference between cemented and non-cemented junction. This difference was not statistically significant (p < 0.18). CONCLUSION: The present study showed that the low porous cement was able to significantly influence the stiffness of the augmented odontoid screw fixation in vitro, although further in vivo clinical studies should be undertaken. Our results suggest that only a small amount of non-porous cement is needed to restore stiffness at least to its pre-fracture level and this can be achieved with the injection of 0.7-1.2 ml of cement. These slides can be retrieved under Electronic Supplementary Material.
Keywords: fraktury páteře; Odontoid Process; dens axis; Fracture Fixation, Internal; vnitřní fixace fraktury; Finite element; Aged; senioři; kostní cementy; Odontoid; Spine; kostní šrouby; lidé; Fracture; Bone cement; Humans; Spinal Fractures; Bone Cements; Bone Screws